2020
DOI: 10.1002/brb3.1961
|View full text |Cite
|
Sign up to set email alerts
|

Increased transcription of TSPO, HDAC2, and HDAC6 in the amygdala of males with alcohol use disorder

Abstract: Introduction Repeated exposure to high doses of alcohol triggers neuroinflammatory processes that contribute to craving and mood dysfunction in alcohol use disorder (AUD). The upregulation of the translocator protein (TSPO) is considered a biomarker of neuroinflammation, and TSPO ligands have been used as neuroimaging biomarkers of neuroinflammation. Epigenetic mechanisms are also implicated in neuroinflammatory responses to alcohol, and elevated expression of HDAC2 and HDAC6 has been reported in the brain of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Interestingly, they found greater HDAC2 and HDAC6 mRNA levels in the amygdala tissue of AUD individuals compared to controls but not in NAc, hippocampal, or PFC tissues. The elevation of both TSPO and HDAC2 and HDAC mRNA levels in amygdala tissue perhaps indicates the unique sensitivity of the amygdala to epigenetic regulation and neuroinflammation in response to chronic alcohol exposure ( 47 ). The discrepancy across in vivo and in vitro studies on TSPO levels on chronic alcohol exposure unfolds various role played by TSPO including neuroinflammation, steroid hormone synthesis, various intracellular functions like apoptosis, oxidative stress, as well as its ability to regulate development of tolerance to alcohol ( 48 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, they found greater HDAC2 and HDAC6 mRNA levels in the amygdala tissue of AUD individuals compared to controls but not in NAc, hippocampal, or PFC tissues. The elevation of both TSPO and HDAC2 and HDAC mRNA levels in amygdala tissue perhaps indicates the unique sensitivity of the amygdala to epigenetic regulation and neuroinflammation in response to chronic alcohol exposure ( 47 ). The discrepancy across in vivo and in vitro studies on TSPO levels on chronic alcohol exposure unfolds various role played by TSPO including neuroinflammation, steroid hormone synthesis, various intracellular functions like apoptosis, oxidative stress, as well as its ability to regulate development of tolerance to alcohol ( 48 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on postmortem markers of inflammation revealed increased markers of microglia in the cingulate cortex, VTA, amygdala, and midbrain of individuals with alcohol use disorder (AUD) compared with those of nondependent controls ( 9 , 10 ). They also showed higher expression of TLRs and downstream signaling cascade NF-κB in the orbital frontal cortex and higher concentration of proinflammatory cytokines (i.e., monocyte chemoattractant protein-1) in the VTA, hippocampus, and amygdala ( 10 12 ).…”
Section: Introductionmentioning
confidence: 99%